The changing face of pharmacy practice and the need for a new model of pharmacy education - (:unkn) unknown (E-Flow Medknow Publications, 2013)
Pharmacy profession has evolved from its conventional and traditional drug focused basis to an advanced patient focused basis over the years. In the past century the pharmacists were more involved in compounding and manufacturing of medicines, but this role has significantly reduced over time. This advancement in the role of pharmacist calls for them to be the part of the broader health care team working for providing better health care for the patients, thus contributing in achieving the global millennium development goals. To match up, the role of today's pharmacists needs to be expanded to include pharmaceutical care concepts, making the pharmacist a health care professional rather than a drug seller in a commercial enterprise. Therefore, pharmacy schools should prepare a program that has competence with the changing role of the pharmacist. The education should provide ability for critical thinking, improve problem-solving skills and decision making during pharmacotherapy. The student should be trained to create, transmit, and apply new knowledge based on cutting-edge research in the pharmaceutical, social, and clinical sciences; collaborate with other health professionals and learn to enhance the quality of life through improved health for the people of local society and as well as the global community. © 2013, InPharm Association, Published by Reed Elsevier India Pvt. Ltd. All rights reserved.
Keywords: Pharmaceutical care; Pharmacist; Pharmacy education; Rational pharmacotherapy; Rational use of medicine